Business Development Strategy for Chocolate Rangginang Products at Kang Asrok’s Micro Small Business in Banjar City West Java Province - Shafira Mellania Rahayu Pamungkas; Yusalina; Ratna Winandi (Jurnal Manajemen & Agribisnis, 2022)
Kang Asrok is a small micro-business engaged in the food processing industry, namely rangicok, which uses rangginang as a basic ingredient that is innovated with various flavors to become today's food that maintains the existence of traditional food. This study aims to analyze internal and external environmental factors: weaknesses, strengths, threats, and opportunities, formulate strategic alternatives and formulate business strategy priorities that can be a recommendation for Kang Asrok. This study uses primary data from the questionnaire of 3 experts, observation and interview with the owner, and an online survey of 20 respondents. This study uses a three-stage analysis consisting of the input stage, the matching stage, and the decision stage. This study was conducted using analysis tools such as the SWOT matrix, IFE, and EFE matrix, IE matrix, and QSP matrix. The results showed that Kang Asrok was in quadrant IV, which means the right strategy is growth and build. Based on the QSP matrix, the right strategy to be applied is market penetration to create brand awareness of the community towards the product got a STAS score of 5,30. Keywords: processing industry, QSPM, traditional food, SWOT